Kedudukan Peradilan Pajak dalam Sistem Peradilan di Indonesia: KEDUDUKAN PERADILAN PAJAK DALAM SISTEM PERADILAN DI INDONESIA - Mushawirya, Rustian (Mendapo: Journal of Administrative Law, 2024)
This article was prepared against the background of the unclear position of the Tax Court in the judicial system in Indonesia. This research uses normative juridical methods which are supported by data collection techniques using library research intended to obtain secondary data. In conducting this research, the type of research used by the author is normative juridical, or also often called normative legal research. This type of research was chosen to obtain theoretical matters, principles, conceptions, legal doctrines, and legal rules related to the position of tax courts in the Indonesian judicial system. The problem studied in this research is the position of the Tax Court in the judicial system in Indonesia, and whether the tax dispute resolution mechanism according to Undang-Undang Nomor 14 of 2002 is in line with the principles of judicial power in Indonesia. This research uses a descriptive analytical method with a normative juridical approach supported by an empirical juridical approach. The data collection technique is to use library research intended to obtain secondary data. This data is also supported by using field studies as primary data. The research results show that the position of the Tax Court in the judicial power structure is a deviation from Pasal 24 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945.